If r☉s = rs + r + s, then for what value of s is r : Quant Question Archive [LOCKED]
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 17 Jan 2017, 10:24

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If r☉s = rs + r + s, then for what value of s is r

Author Message
Manager
Joined: 11 May 2007
Posts: 106
Followers: 1

Kudos [?]: 37 [0], given: 0

If r☉s = rs + r + s, then for what value of s is r [#permalink]

### Show Tags

27 Nov 2007, 15:22
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

If r☉s = rs + r + s, then for what value of s is r ☉s equal to r for all values of r?
(A) –1
(B) 0
(C) 1
(D) 1/(r+1)
(E) r
CEO
Joined: 29 Mar 2007
Posts: 2583
Followers: 19

Kudos [?]: 420 [0], given: 0

### Show Tags

27 Nov 2007, 15:51
yogachgolf wrote:
If r☉s = rs + r + s, then for what value of s is r ☉s equal to r for all values of r?
(A) –1
(B) 0
(C) 1
(D) 1/(r+1)
(E) r

rs+r+s=r

I get B. Lets say r= 5, -2, or 0. (mix up the values)

if r*s=rs+r+s. and s=0. then try rs+r+s=r. Which values work?

A: 5(-1)+5+-1=5? No Used 5 for r
B: -2(0)+-2+0=-2? Yes Used -2 for r
C: -2+-2+1=-2? No Used -2 for r
D: 5/6 +5 +1/6 =5? NO used 5 for r
E: No need for values as we can see that r^2+2r is not equal to r if r is anything but 0.

There is another way that I just found that is much easier.

rs+r+s=r ---> s(r+1)+r=r ---> s(r+1)=0 s=0 r=-1.

B.
SVP
Joined: 28 Dec 2005
Posts: 1575
Followers: 3

Kudos [?]: 147 [0], given: 2

### Show Tags

16 Dec 2007, 08:57
i am getting A.

r?s=rs+r+r=r(s+2)

you want r?s=r, then you should set s+2 to give 1, so that you are only left with r.

s+2=1, s=-1.
CEO
Joined: 17 Nov 2007
Posts: 3589
Concentration: Entrepreneurship, Other
Schools: Chicago (Booth) - Class of 2011
GMAT 1: 750 Q50 V40
Followers: 545

Kudos [?]: 3551 [0], given: 360

### Show Tags

16 Dec 2007, 09:38
pmenon wrote:
r?s=rs+r+r=r(s+2)

In original question: r?s=rs+r+s

rs+r+s=r ==> s(r+1)=0 is correct for any r only at s=0.
16 Dec 2007, 09:38
Display posts from previous: Sort by